Catheter induced hypospadias, urethral trauma and penile abscess in completely recoverable neurological afflictions: preventable entities - Sandhu, Harbhupinder S.; Singh, Harjinder; Sharma, Amarjit (International Journal of Research in Medical Sciences, 2020)
Background: Catheter associated complications are very common in the emergency departments of medicine, general surgery, orthopaedics and in community. They mostly occur in patients with neurological afflictions because of inexperience of the first handlers as they lack the insight of altered physiology and anatomy in the lower urinary tract because of neurological lesions and also because of an inadequate advice at the time of discharge regarding the catheter care. Objectives of this study were to find the prevalence of per-urethral catheter associated injuries in patients with neurological lesions in a tertiary care centre of south-eastern Punjab and their prevention in completely recoverable neurological afflictions. Methods: This is a cross-sectional observational study conducted in urology department from 1st August 2017-31st August 2018. The data was taken from medicine, general surgery and orthopedic emergency departments. A total of 82 patients were taken from 19-78 years and 49 patients had per-urethral catheter placement. Analysis was done using Statistical Program of Special Sciences, version 20. Results: It was observed that overall neurological lesions are more common in males (80.48%) as compared to females (19.51%) and distributed over an age range of 19-84 years in both sexes. Out of total patients, 59.75% required per urethral catheterization. The prevalence of per-urethral catheter associated complications was 20.40%. Conclusions: Insertion of per-urethral catheter is a simple procedure but an error of omission on the part of health professionals’ results in a serious complication in a neurological patient. Proper insertion technique and catheter care are to be followed to prevent avoidable complications in this subset of patients.